2015
DOI: 10.1016/j.aller.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of profitability in the diagnosis of allergy to beta-lactam antibiotics

Abstract: In the series studied, diagnosis of allergy to beta-lactams was confirmed in 6% of patients (2.3% of paediatric patients). After analysing results and cost of the study we believe that we should propose a specific diagnostic algorithm in those paediatric patients without suspected IgE-mediated ADR, and for those patients direct DPT should be conducted. This will reduce cost/patient (-34.9%), time of resolution and absenteeism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…The identified cost savings with forgoing the skin test was greater in this study than reported in one prior study that identified a reduction by $69 (35% lower) if no skin test was performed. 48 While complete evaluation with skin testing is preferred, especially for patients with higher risk allergy histories, oral challenge only can be considered for patients with mild allergy histories or when there are no personnel trained to perform and interpret skin tests. Indeed, through use of challenge-only evaluations, 818 Canadian children with histories of amoxicillin allergy were safely challenged to amoxicillin without skin testing, and in that study saved their health system $182,393 compared to full skin testing with oral challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The identified cost savings with forgoing the skin test was greater in this study than reported in one prior study that identified a reduction by $69 (35% lower) if no skin test was performed. 48 While complete evaluation with skin testing is preferred, especially for patients with higher risk allergy histories, oral challenge only can be considered for patients with mild allergy histories or when there are no personnel trained to perform and interpret skin tests. Indeed, through use of challenge-only evaluations, 818 Canadian children with histories of amoxicillin allergy were safely challenged to amoxicillin without skin testing, and in that study saved their health system $182,393 compared to full skin testing with oral challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that most children (more than 90%) are not confirmed as allergic, this algorithm is heavily resource‐intensive and time‐consuming or could even lead to a number of wrong diagnoses of drug hypersensitivity due to uncertain predictive values of skin tests. In recent years, a number of papers have challenged the academic guidelines and have explored the feasibility of performing OPT without skin tests in children with suspicion of a benign non‐immediate reaction . In spite of reported good results, economic savings, and observed satisfaction by parents and doctors, this attitude is still debated and some authors still consider performing intradermal tests, mainly due to fear of severe reactions during OPT .…”
Section: What To Do With a Child With Suspected Blh In A Specialized mentioning
confidence: 99%
“…In recent years, a number of papers have challenged the academic guidelines and have explored the feasibility of performing OPT without skin tests in children with suspicion of a benign non-immediate reaction. 4,[6][7][8][9] In spite of reported good results, economic savings, and observed satisfaction by parents and doctors, this attitude is still debated and some authors still consider performing intradermal tests, mainly due to fear of severe reactions during OPT. 10 As a result, in current clinical practice, things are not so clear and very different approaches are followed by practicing clinicians.…”
Section: What To Do With a Child With Suspected Blh In A Specializementioning
confidence: 99%
“…Recently, the Pediatric Task Force of the EAACI Drug Allergy Interest Group suggested the use of DPT without prior skin testing in the cases of non-immediate mild cutaneous reactions [ 45 ]. This approach may also reduce the cost of drug allergy algorithm, up to 35% per patient [ 46 ].…”
Section: Pro: the Tip Of The Icebergmentioning
confidence: 99%